2021
DOI: 10.3390/polym13020292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drug Incorporation on the Physico-Chemical Properties of Poly(l-Lactide) Implant Coating Matrices—A Systematic Study

Abstract: Local drug delivery has become indispensable in biomedical engineering with stents being ideal carrier platforms. While local drug release is superior to systemic administration in many fields, the incorporation of drugs into polymers may influence the physico-chemical properties of said matrix. This is of particular relevance as minimally invasive implantation is frequently accompanied by mechanical stresses on the implant and coating. Thus, drug incorporation into polymers may result in a susceptibility to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 74 publications
(74 reference statements)
1
10
0
Order By: Relevance
“…The tensile strain value also decreased with 30 mg of J addition (20.67 ± 4.90%), however, it still had a higher value compared to the PLA ( w / v ) strain value. These results are in agreement with the literature data [ 24 , 25 ]. It can be concluded that the J addition induced an increase in the tensile strength, making the scaffold more elastic.…”
Section: Resultssupporting
confidence: 94%
“…The tensile strain value also decreased with 30 mg of J addition (20.67 ± 4.90%), however, it still had a higher value compared to the PLA ( w / v ) strain value. These results are in agreement with the literature data [ 24 , 25 ]. It can be concluded that the J addition induced an increase in the tensile strength, making the scaffold more elastic.…”
Section: Resultssupporting
confidence: 94%
“…The T g values are similar in bulk and empty particles but increase with drug loading due to the incorporation of dexamethasone that has a high T g (117 °C). The observed increase in T g of the drug-loaded particles was expected with incorporating a high T g drug . A single T g value was observed during the second heat, indicating polymer–drug miscibility for all formulations prepared after temperature processing.…”
Section: Resultsmentioning
confidence: 69%
“…The used micro-stent coating material PLLA is a well-known and established coating material for cardiovascular devices and controlled drug release systems [11] including direct mixing or adsorption of antibiotics or drug encapsulation in microspheres or coreshell porous nanofibers to avoid burst-release. [12][13][14] Therefore, this material is an ideal candidate for the validation of our in vivo model for testing antimicrobial materials in the bloodstream for cardiovascular devices.…”
Section: Discussionmentioning
confidence: 99%